ANALISIS MARK-UP DALAM TRANSAKSI MURABAHAH PADA PERBANKAN SYARIAH - Rahmadini, Salsa; Rohadatul Aisy, Zahra; Susanti, Susi; Alfiah Insani, Nurul; Sundari, Asri (Pelita Nusa Jurnal, published by the Institute for Research and Community Service (LP2M) of the Pelita Nusa Islamic Religious College West Bandung (STAI PENUS), 2024)
Increasing community needs drive the need for alternative financing that is in accordance with sharia principles. Murabahah as one of the superior products in sharia financial institutions, is the main choice because it can meet sharia needs with a low risk of loss. However, obstacles such as Mark-up s in murabahah transactions raise questions about whether they are in accordance with sharia principles. This study uses a qualitative descriptive approach to analyze the concept of Mark-up in murabahah transactions from a sharia perspective. Based on the results of the analysis, murabahah transactions in sharia banking involve various processes, including identifying customer needs, assessing feasibility, murabahah contracts, purchasing goods, selling to customers, and monitoring installment payments. Even though sharia banks act as providers of costs in murabahah financing, all related risks are borne by the customer in accordance with the agreement.